2015
DOI: 10.1242/jcs.165571
|View full text |Cite
|
Sign up to set email alerts
|

Actin depolymerisation and crosslinking join forces with myosin II to contract actin coats on fused secretory vesicles

Abstract: In many secretory cells actin and myosin are specifically recruited to the surface of secretory granules following their fusion with the plasma membrane. Actomyosin-dependent compression of fused granules is essential to promote active extrusion of cargo. However, little is known about molecular mechanisms regulating actin coat formation and contraction. Here, we provide a detailed kinetic analysis of the molecules regulating actin coat contraction on fused lamellar bodies in primary alveolar type II cells. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 74 publications
2
59
0
Order By: Relevance
“…Actin coating is necessary for these vesicles to release their cargo, however the precise mechanism triggering this actin coat during vesicular release remains unclear (Miklavc et al, 2009) Similarly, actin depolymerisation and myosin II action counteract actin coats on fused lamellar bodies in primary alveolar type II cells (Miklavc et al, 2015). The Actomyosin-coat on such fused granules is essential to promote active extrusion of cargo.…”
Section: Actomyosin Assembly On Vesicles Undergoing Fusion (Actin Coamentioning
confidence: 99%
“…Actin coating is necessary for these vesicles to release their cargo, however the precise mechanism triggering this actin coat during vesicular release remains unclear (Miklavc et al, 2009) Similarly, actin depolymerisation and myosin II action counteract actin coats on fused lamellar bodies in primary alveolar type II cells (Miklavc et al, 2015). The Actomyosin-coat on such fused granules is essential to promote active extrusion of cargo.…”
Section: Actomyosin Assembly On Vesicles Undergoing Fusion (Actin Coamentioning
confidence: 99%
“…2, middle). Actin has further been shown to regulate exocytosis in other secretory cell types in partnership with myosin (2,12,79,82). The pharmacological agents latrunculin and jasplakinolide, that depolymerize and stabilize F-actin, respectively, differentially influence insulin secretion.…”
Section: Letting the Skeleton Out Of The Closetmentioning
confidence: 99%
“…2, event 9). NMII and F-actin are recruited to coat the surface of dense-core granules during their fusion with the plasma membrane (79), and contraction of this coat drives discharge of granule contents (82,89). In transformed ␤-cells, MLCK colocalizes with granules with activation of PKC leading to a common shift toward the periphery (155), and F-actin and NMII heavy chain A (MHCIIA) redistribute toward contact points in response to stimulation by KCl (149) (Fig.…”
Section: Letting the Skeleton Out Of The Closetmentioning
confidence: 99%
“…Actin along the cortex of cells is thought to serve as a barrier to prevent premature fusion of secretory granules with the apical PM in certain 1 systems (Brown et al, 2011;Giner et al, 2005;Trifaró et al, 2008). Other studies have shown that actin is essential for proper fusion pore expansion (Larina et al, 2007) and vesicle compression to expel large viscous cargo (Jerdeva et al, 2005;Miklavc et al, 2015Miklavc et al, , 2012Nightingale et al, 2011). There is also a suggested role for transient actin cables in directing vesicles to the apical PM (Geron et al, 2013).…”
Section: Regulated Exocytosismentioning
confidence: 99%
“…Previous cell culture studies have provided evidence that actin present on secretory vesicles generates the compressive forces necessary to mediate secretion of cargo (Jerdeva et al, 2005;Miklavc et al, 2015Miklavc et al, , 2012Nightingale et al, 2011). Additionally, intravital imaging of secretion in rodent salivary glands using the actin inhibitors latrunculin A (LA) or cytochalasin D (CD) has demonstrated that disruption of actin polymerization interferes with the gradual collapse of the secretory vesicles in vivo (Masedunskas et al, 2011).…”
Section: Overview Of Regulated Exocytosis In Drosophilamentioning
confidence: 99%